Graphene quantum dot-decorated carbon electrodes for energy storage in vanadium redox flow batteries. Issue 14 (29th March 2020) - Daugherty, Michael C.; Gu, Siyong; Aaron, Doug S.; Kelly, Ryan E.; Ashraf Gandomi, Yasser; Hsieh, Chien-Te
Abstract : Nitrogen-doped graphene quantum dots (GQDs) and graphitic carbon nitride (g-C3 N4 ) quantum dots are synthesized via a solid-phase microwave-assisted (SPMA) technique. Abstract : Nitrogen-doped graphene quantum dots (GQDs) and graphitic carbon nitride (g-C3 N4 ) quantum dots are synthesized via a solid-phase microwave-assisted (SPMA) technique. The resulting GQDs are deposited on graphite felt (GF) and are employed as high-performance electrodes for all-vanadium redox flow batteries (VRFBs). The SPMA method is capable of synthesizing highly oxidized and amidized GQDs using citric acid and urea as the precursor. The as-prepared GQDs contain an ultrahigh O/C (56–61%) and N/C (34–66%) atomic ratio, much higher than the values reported for other carbon-based nano-materials ( e.g. oxidized activated carbon, carbon nanotubes, and graphene oxide). Three types of quantum dots, having an average particle size of 2.8–4.2 nm, are homogeneously dispersed onto GF electrodes, forming GQD/GF composite electrodes. Through deposition of GQDs onto the electrode structure, the catalytic activity, equivalent series resistance, durability, and voltage efficiency are improved. The capacity utilization using GQD/GF electrode is substantially enhanced (∼69% increase within 40 cycles). The improved performance is attributed to the synergistic effect of GQDs containing oxygen functionalities (epoxy, phenolic and carboxylic groups) and lattice N atoms (quaternary, pyrrolic and pyridinic N) which result in enhanced wettability and increased electrochemical surface area providing increased reaction sites.